2012
DOI: 10.1007/s10096-012-1694-7
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic therapy in necrotising external otitis: case series of 32 patients and review of the literature

Abstract: Necrotising external otitis (NEO) is a rare but severe bone infection, usually due to Pseudomonas aeruginosa, the management of which is not standardised. Systemic antibiotic therapy is usually prescribed for at least 6 weeks, but no review has been published on this topic. We report our experience and have reviewed the literature regarding antibiotic therapy in NEO. Here we describe a case-series of consecutive NEO cases seen over an 8-year period (2004-2011) in a French tertiary-care teaching hospital. Since… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
17
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 33 publications
6
17
1
Order By: Relevance
“…A French study of 32 cases of necrotizing otitis externa found that mean length of stay (18.2±8.7 vs. 11.6±6.9 days, p=0.03) and duration of antibiotic therapy (9.4±3.2 vs. 5.8±0.7 weeks, p<0.001) were significantly lower after 2009 when a management protocol for necrotizing otitis externa was introduced. This supports our data and our conclusions [9] . Our mortality rate is significantly lower (2.4%) than that of other studies (14.8%), possibly due to the fact that these patients are managed jointly with infectious diseases [5] .…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…A French study of 32 cases of necrotizing otitis externa found that mean length of stay (18.2±8.7 vs. 11.6±6.9 days, p=0.03) and duration of antibiotic therapy (9.4±3.2 vs. 5.8±0.7 weeks, p<0.001) were significantly lower after 2009 when a management protocol for necrotizing otitis externa was introduced. This supports our data and our conclusions [9] . Our mortality rate is significantly lower (2.4%) than that of other studies (14.8%), possibly due to the fact that these patients are managed jointly with infectious diseases [5] .…”
Section: Discussionsupporting
confidence: 94%
“…The most common presenting features found in our study of otalgia and otorrhea are in common with other larger case series and highlight the need for high clinical suspicion in immunocompromised or diabetic patients with these symptoms [9] . Facial nerve palsy was a less common presentation in the group post-intervention, although this was not statistically significant, and may have been due to the fact that post-intervention, there was greater awareness of necrotizing otitis externa, so these patients were managed earlier, before developing complications such as facial nerve palsy.…”
Section: Discussionsupporting
confidence: 84%
“…However, conclusive prognostic factors are yet to be identified. The emergence of fluoroquinolonesresistant and multidrug resistant pseudomonas organisms have created difficulty in developing consensus on the optimal choice of antibiotics and duration of therapy (Pulcini et al, 2012;Berenholz et al, 2002). The study found diabetes as the underlying debilitating disease in 53% of the patients, whereas 29% were immune depressed due to HIV infection similar to other reports (Franco-Vidal et al, 2007;Martel et al, 2000).…”
Section: Discussionsupporting
confidence: 74%
“…The study found diabetes as the underlying debilitating disease in 53% of the patients, whereas 29% were immune depressed due to HIV infection similar to other reports (Franco-Vidal et al, 2007;Martel et al, 2000). However higher diabetic figures of 80 to 95% have been reported (Lee et al, 2011;Loh and Loh, 2013;Pulcini et al, 2012;Chen et al, 2011).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation